Cerium oxide nanoparticles impact on sepsis-induced cerebral injury: Deciphering miRNA / NF-κB/TLR signalling pathway: CeO2 NPs impact on sepsis-induced cerebral injury - Abdulaal, Wesam H.; Helmi, Nawal; Hamza, Amal; Salem, Neveen A. (Cellular and Molecular Biology, 2024)
Sepsis is regarded as an inflammatory syndrome that consists of complex biochemical and pathophysiological dysregulation, brought on by endogenous factors in response to systemic infection. Sepsis can cause short- and long-term cerebral injury. Cerium oxide nanoparticles (CeO2 NPs) have been reported to possess both anti-inflammatory and antioxidative properties. The current study investigated the potential role of cerium oxide nanoparticles in the management of sepsis-induced brain injury. To achieve this target, forty male albino rats were divided into 4 groups, ten rats each. Group (i) set as a shame group. Group (ii) set as shame group administrated CeO2 NPs. Group (iii) septic group treated with saline and Group (iv) septic group treated with CeO2 NPs. The sepsis model in rats was induced by cecal ligation and puncture (CLP). Results showed CeO2 NPs administration resulted in significant improvement in the survival rate of rats, suppression in serum sepsis biomarkers (CRP, ESM-1, PCT and D- dimer), amelioration of brain inflammatory mediators (TNF-α- IL-6, NF-kB and LTB4) as well as apoptotic markers (Cas-3 and BAX). Furthermore, immunomodulation of miRNAs expression (155,124 and 146a). These findings demonstrate a promising pivotal role of CeO2 NPs treatment in alleviating the deleterious effects induced by sepsis in the brain